2018
DOI: 10.1186/s13568-018-0619-y
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of lactobacilli isolated from Armenian dairy products: an effective strain and its probable nature

Abstract: Different strains of lactobacilli isolated from Armenian dairy products (matsoun, sour cream and different types of cheeses), were studied for antifungal activity. Lactobacillus rhamnosus MDC 9661 strain was shown to have inhibitory activity against Penicillium aurantioviolaceum and Mucor plumbeus growth. Bacterial cell-free supernatant didn’t show antifungal activity. The L. rhamnosus antifungal activity was stable to the wide range of pH from 3 to 10. This activity was high after treatment with both low temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The proteinaceous nature of their antibacterial components had been shown. The bacteriocineous nature of antibacterial components synthesized by LAB associations should be confirmed (Movsesyan et al 2010; Bazukyan et al 2018). So we can only speculate that in the combinations they synthesized some antibacterial components with proteinaceous nature, too.…”
Section: Resultsmentioning
confidence: 97%
“…The proteinaceous nature of their antibacterial components had been shown. The bacteriocineous nature of antibacterial components synthesized by LAB associations should be confirmed (Movsesyan et al 2010; Bazukyan et al 2018). So we can only speculate that in the combinations they synthesized some antibacterial components with proteinaceous nature, too.…”
Section: Resultsmentioning
confidence: 97%
“…To determine the antifungal activity, the six most active LAB strains were selected, and from these strains 15 different combinations were created according to Bazukyan et al [19] and Matevosyan et al [20]. The antifungal activity of E. durans was not studied, since it is the reference strain from INRA (Nantes, France), the antifungal activity of which was shown by Ahmadova et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…The suspension of fungal/molds spores (the amount was 10 4 per ml) was dropwise applied on the surface of media after 48 h LAB cultivation. The suspensions of fungal spores were prepared according to Bazukyan et al [19]. The antifungal activity was detected in the absence of fungal/molds growth on the surface of the medium (quantitative test).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms of action of antibacterial activity against other pathogens such as Shigella sonnei was due to the production of organic acids and macromolecules involved in inhibition [2]. Studies have also shown that lactic acid bacteria have a vast amount of bioactive compounds that are beneficial as antifungal [3], antibiotic-resistant uropathogens [3], and other human pathogenic bacteria [4], in addition to other potential uses such as anti-cancer, anti-hypertensive, anti-thrombotic, lowering of cholesterol [5], anti-oxidant, and immunomodulation from food proteins [6] in the receptors of the gut epithelium [7]. Further assessment and classification of these bacteria as potential probiotic typically requires in vitro and in vivo study.…”
Section: Introductionmentioning
confidence: 99%